FACTORS ASSOCIATED WITH ANXIETY LEVEL OF TRIMESTER III PRIMIGRAVIDA PREGNANT WOMEN IN MENUR HEALTH CENTER SURABAYA - Sumaiyah Mat; Makdalena Kambu; Lutfi Agus Salim (Universitas Airlangga, 2023)
Pregnancy and childbirth are normal things experienced by women, but this still has a high risk and burden women. The purpose of this study is to determine the associated factors of anxiety level among pregnant women in the early third trimester inÂ the Surabaya City Health Service Center Menu. This research is an observational study, which means that it is carried out by conducting field observations with a cross-sectional design and taking samples with a convenient sampling technique of 44 people. Our findings show that the anxiety level in pregnant women with mild levels of primigravida in the first 3 months was reported among 19 people (43.2%) and an average high anxiety level of up to 25 people (56.8%). The analysis was carried out in two dimensions using the Chi-Square test which showed a p value of 0.002. Thus the relationship between the husband's support and anxiety in the third trimester of pregnancy at the Surabaya City Health Service Center is closely related. Therefore, it is suggested that a husbandÂ to provide full support to his wife in the third-trimester primigravida because this can reduce anxiety.